1999
DOI: 10.1038/sj.mp.4000572
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and depression: fortuitous or causative association?

Abstract: There is an increasingly impressive database concerning the possible involvement of cytokines in depression and their role in the therapeutic effects of antidepressants. Based on the discussions which took place on these issues at a recent meeting held in Roscoff, France, this perspective summarizes in a critical way the evidence in favor of such a possibility, and points out the needs for further research to clarify both the nature of the subtle dysregulations that affect neuroendocrine-immune interactions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(74 citation statements)
references
References 38 publications
4
68
1
1
Order By: Relevance
“…These findings replicate the results of many previous studies, which demonstrated that activation of the immune system by LPS, as well as other immune challenges, induces a reduction in appetite and body weight, suppres- sion of locomotor, exploratory, and social activity, fatigue and malaise, impairment in cognitive abilities, reduced libido and sexual behavior, and anhedonia (Anisman and Merali 1999;Dantzer et al 1999;Maier and Watkins 1998;Yirmiya 1996;Yirmiya et al 1994Yirmiya et al , 1999. Our results also demonstrate that LPS produced a marked depletion of CRH-41 ME content, which reflects its release into the portal vessels (Chappell et al 1986), with a concomitant elevation in plasma corticosterone levels.…”
Section: Discussionsupporting
confidence: 90%
“…These findings replicate the results of many previous studies, which demonstrated that activation of the immune system by LPS, as well as other immune challenges, induces a reduction in appetite and body weight, suppres- sion of locomotor, exploratory, and social activity, fatigue and malaise, impairment in cognitive abilities, reduced libido and sexual behavior, and anhedonia (Anisman and Merali 1999;Dantzer et al 1999;Maier and Watkins 1998;Yirmiya 1996;Yirmiya et al 1994Yirmiya et al , 1999. Our results also demonstrate that LPS produced a marked depletion of CRH-41 ME content, which reflects its release into the portal vessels (Chappell et al 1986), with a concomitant elevation in plasma corticosterone levels.…”
Section: Discussionsupporting
confidence: 90%
“…Depression also appears to have an immune substrate, which has been discussed extensively elsewhere. 50,51 Of interest, an association between depression and atopy has been recently reported in the Northern Finland 1966 Birth Cohort. 52,53 It is noteworthy that CRHR1 has a key role in inflammation, 54,55 and that CRHR1 antagonists, which have been used to treat depression, 34,35 also suppress peripheral inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] Antidepressants are known to modulate inflammatory responses after chronic administration, in a time course that is reminiscent of the time frame of antidepressant effects and they also confer protection against cytokine-induced depressive-like biological and behavioral changes. 50,51,[59][60][61] Moreover, concentrations of circulating immune mediators have been found to be elevated in depression. 62,63 Future studies should examine whether there is an interaction between the therapeutic effects of CRHR1 on inflammation and depression or if these are independent of each other.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because several key functions that have been related to the CNS actions of cytokines, such as sleep, food intake, body weight regulation, cognition, behavior, temperature and neuroendocrine transduction, 20 are known to be dysregulated in major depression. In the next article in this issue Dantzer and colleagues provide further discussion on the role of cytokines in depressive disorder, 90 and in a News & Views and accompanying Image in this issue, PlataSalamán and Turrin discuss in broader terms the role of CNS cytokines in neurological and psychiatric disorders. 91,92 …”
Section: Discussionmentioning
confidence: 99%